A New Yeast Peroxin, Pex36, a Functional Homolog of Mammalian PEX16, Functions in the ER-to-Peroxisome Traffic of Peroxisomal Membrane Proteins. Issue 23 (24th November 2017) - Farré, Jean-Claude; Carolino, Krypton; Stasyk, Oleh V.; Stasyk, Olena G.; Hodzic, Zlatan; Agrawal, Gaurav; Till, Andreas; Proietto, Marco; Cregg, James; Sibirny, Andriy A.; Subramani, Suresh
Abstract: Peroxisomal membrane proteins (PMPs) traffic to peroxisomes by two mechanisms: direct insertion from the cytosol into the peroxisomal membrane and indirect trafficking to peroxisomes via the endoplasmic reticulum (ER). In mammals and yeast, several PMPs traffic via the ER in a Pex3- and Pex19-dependent manner. In Komagataella phaffii (formerly called Pichia pastoris ) specifically, the indirect traffic of Pex2, but not of Pex11 or Pex17, depends on Pex3, but all PMPs tested for indirect trafficking require Pex19. In mammals, the indirect traffic of PMPs also requires PEX16, a protein that is absent in most yeast species. In this study, we isolated PEX36, a new gene in K. phaffii, which encodes a PMP. Pex36 is required for cell growth in conditions that require peroxisomes for the metabolism of certain carbon sources. This growth defect in cells lacking Pex36 can be rescued by the expression of human PEX16, Saccharomyces cerevisiae Pex34, or by overexpression of the endogenous K. phaffii Pex25. Pex36 is not an essential protein for peroxisome proliferation, but in the absence of the functionally redundant protein, Pex25, it becomes essential and less than 20% of these cells show import-incompetent, peroxisome-like structures (peroxisome remnants). In the absence of both proteins, peroxisome biogenesis and the intra-ER sorting of Pex2 and Pex11C are seriously impaired, likely by affecting Pex3 and Pex19 function. Graphical abstract: Image 1 Highlights: Characterization of a new peroxisomal membrane protein, Pex36 in K. phaffii Pex36 shares some functional homology with human Pex16 and S. cerevisiae Pex34. Pex25 and Pex36 are redundant proteins and cells lacking both are synthetic lethal. Pex25 and Pex36 are required for the ER-to-peroxisome targeting of Pex2 and Pex11C. The complex between Pex3 and Pex19 is impaired in the absence of both Pex25 and Pex36.